مظاهر انعكاس استخدام المراهقين لمواقع التواصل الاجتماعي الفيسبوك على تحصيل الدراسي - مشقق كوثر; د/نوعي عبد القادر (جامعة عمار ثليجي الاغواط, 2023)
يعتبر الإعلام المدرسي نشاط تربوي متواصل وهادف بغرض تدعيم معارف التلميذ بكل ما يتعلق بالحياة المدرسية والمهنية، بغية إدماجه مع مختلف المستلزمات التربوية الاجتماعية والاقتصادية ومساعدته على التزود بمهارات وكفاءات تساهم في تنمية ميوله وتطوير اهتماماته لتشكيل اختياراته وصياغة تصورات دراسية ضمن مشروع دراسي يتلاءم مع قدراته وطموحاته والأفاق المسطرة للتخصصات والمسارات الدراسية المختلفة . من هنا جاءت فكرة الدراسة التي هدفت إلى معرفة مدى فاعلية الإعلام المدرسي في تصحيح رغبات التلاميذ وفق ملمحهم الدراسي و مساهمته في حث التلاميذ على الاستعلام الذاتي حول المسارات والتخصصات الدراسية، والى أي مستوى يمكن أن تتباين درجة التأثير المنتظرة من الإعلام المدرسي انطلاقا من اختلاف التخصص الدراسي . أجريت هذه الدراسة بمتوسطة بلهوشات بوزيد بلدية تاجموت ولاية الاغواط ، وتم استخدام في هذه الدراسة المنهج الوصفي الاستطلاعي وبلغت عينة الدراسة 7 تلاميذ من اصل 70 تلميذ ، كما استخدمنا بطاقة الرغبات كأداة لجمع البيانات. Abstract: School media is a continuous and purposeful educational activity with the aim of strengthening the student’s knowledge of everything related to school and professional life, in order to integrate him with the various educational, social and economic requirements and help him to acquire skills and competencies that contribute to the development of his inclinations and the development of his interests to form his choices and formulate study perceptions within a study project that is compatible with his abilities, ambitions and horizons Ruler for different disciplines and study paths. From here came the idea of the study, which aimed to know the effectiveness of school media in correcting students’ desires according to their academic profile and its contribution to urging students to self-inquiry about academic paths and specializations, and to what level the degree of influence expected from school media can vary based on the different academic specialization . This study was conducted in the middle school of Belhouchat Bouzid, municipality of Tajmot, Laghouat province, and the descriptive exploratory method was used in this study. The sample of the study was 7 students out of 70 students. We also used the Desire Card as a tool for data collection.